1996
DOI: 10.1523/jneurosci.16-08-02829.1996
|View full text |Cite
|
Sign up to set email alerts
|

Impaired classical eyeblink conditioning in cerebellar-lesioned and Purkinje cell degeneration (pcd) mutant mice

Abstract: Converging lines of evidence from rabbits, rats, and humans argue for the crucial involvement of the cerebellum in classical conditioning of the eyeblink/nictitating membrane response in mammals. For example, selective lesions (permanent or reversible) of the cerebellum block both acquisition and retention of eyeblink conditioning. Correspondingly, electrophysiological and brain-imaging studies indicate learning-related plasticity in the cerebellum. The involvement of the cerebellum in eyeblink conditioning is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
194
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(216 citation statements)
references
References 48 publications
18
194
4
Order By: Relevance
“…Transgenic mice that loose all cerebellar Purkinje cells within the first two months of life perform significantly worse in eyeblink conditioning than their do wild-type litter mates (Chen et al 1996). Purkinje cell loss or cerebellar cortical aspirations do not prevent the acquisition of CRs.…”
Section: Eyeblink Conditioning In Aging Micementioning
confidence: 93%
See 1 more Smart Citation
“…Transgenic mice that loose all cerebellar Purkinje cells within the first two months of life perform significantly worse in eyeblink conditioning than their do wild-type litter mates (Chen et al 1996). Purkinje cell loss or cerebellar cortical aspirations do not prevent the acquisition of CRs.…”
Section: Eyeblink Conditioning In Aging Micementioning
confidence: 93%
“…Purkinje cell loss or cerebellar cortical aspirations do not prevent the acquisition of CRs. Rather loss of the cerebellar cortical machinery normally engaged in acquisition of CRs slows the rate of acquisition (Lavond and Steinmetz 1989;Chen et al 1996).…”
Section: Eyeblink Conditioning In Aging Micementioning
confidence: 99%
“…There was a significant difference in the training condition effect [F(1, 81) ϭ 444.108, P Ͻ 0.0001] and condition ϫ session interaction [F(8, 648) ϭ 119.4, P Ͻ 0.0001] between the two training groups. On the first day of extinction training, there was no significant difference between the two groups that received an additional 4 d of extinction training after 7 d of paired training (days [8][9][10][11] [F(1, 6) ϭ 1.704, P ϭ 0.2396], indicating rapid and successful extinction. The comparison of CR% on the last training day demonstrated a clear difference in the memory state of eyeblink conditioning between the training groups (Fig.…”
Section: Paired But Not Unpaired Groups Acquired a Robust Memory For mentioning
confidence: 99%
“…This hypothesis has been examined repeatedly with lesions (3-7) and inactivation of the AIN (8,9), and in mutant mice with Purkinje cell degeneration (10). Recent observations made using electron microscopy (11) or functional magnetic resonance imaging (12) further support the notion that the basic memory trace is formed in the AIN.…”
mentioning
confidence: 94%
“…Abnormalities in eye-blink conditioning have been associated with cerebellar alterations (49). Accordingly, we previously showed that the cerebella of MAO A/B KO, but not MAO A KO, mice exhibit significant reductions of Purkinje cells number and enhancements of the molecular and granule cells layers (16).…”
Section: Mao A/b Ko Mice Showed Enhanced Contextual and Cue Memory Andmentioning
confidence: 96%